The Working Capital Management and ProfitabilityAnalysis on The Leading Dairy Food Industries in Indonesia - Anita Munir (President University Press, 2017)
The main purpose of this study is to analyze trends in the working capital management that impact the profitability of those Indonesian dairy food companies with the highest levels of sales revenue which is listed in Indonesian stock exchange.Working capital management is one of the most important financial decisions in the company that can increase the company’s value. The test was adopted to examine return on equity as the dependent variable and average collection period, day payables outstanding, current ratio as the independent variables. The data were taken by using purposive sampling method with level significant of 5%. The result of multiple linear regression analysis indicated there was a positive significant impact of day payables outstanding and current ratio on return on equity Meanwhile for the average collection period was insignificant negatively impact on the return on equity. Further, in this resarch is suggested that managers in dairy food industries can optimal their return on equity by balancing between profitability and liquidity, and paying more attention on effectiveness of working capital management. In any case, working capital is a particularly important topic in industry due to the continuous development of technology and rapid changes in business environment.